Ordinary Jews : choice and survival during the Holocaust - Finkel, Evgeny 1978- (Princeton University Press, 2017)
Chapter 1. Introduction -- Chapter 2. Setting the stage: Jewish ghettos during the Holocaust -- Chapter 3. What did the Jews know? -- Chapter 4. Cooperation and collaboration -- Chapter 5. Coping and compliance -- Chapter 6. Evasion -- Chapter 7. Resistance -- Chapter 8. Conclusions -- Appendix 1. Data and archival methods -- Appendix 2. Distribution of strategies -- Appendix 3. Beyond the three ghettos: econometric analysis of uprisings